2018
DOI: 10.15407/pts2018.16.120
|View full text |Cite
|
Sign up to set email alerts
|

Data on the bat fauna of the Northern Black Sea Region based on results of the work of bat contact centres

Abstract: Data on the bat fauna of the Northern Black Sea Region based on results of the work of bat contact centres.-P. Panchenko, L. Godlevska.-During 2009-2018, 201 calls were received by the Odesa contact centre, OCC (n = 174, in 143 of them bat species was identified) and the Kyiv contact centre, KCC, from the Northern Black Sea Region (n = 27; 10, with an identified species). The majority of calls (94 %) to the OCC came from Odesa region. The number of calls and its increase in time confirms the demand for bat con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…2015 b; Prylutska & Vlaschenko, 2013;Panchenko & Godlevska, 2018). N. noctula is known as the species forming large hibernation colonies in hundreds of specimens in multi-storey buildings in settlements .…”
Section: Bat Roostsmentioning
confidence: 99%
“…2015 b; Prylutska & Vlaschenko, 2013;Panchenko & Godlevska, 2018). N. noctula is known as the species forming large hibernation colonies in hundreds of specimens in multi-storey buildings in settlements .…”
Section: Bat Roostsmentioning
confidence: 99%
“…Past studies in Ukraine have shown that for the most part bats are encountered as single individuals or occasionally in small groups in winter. Cases of 15-20 individuals in a single group are present but rare (Rebrov 2012;Gashchak et al 2013;Godlevska 2015;Godlevska & Rebrov 2018;Panchenko & Godlevska 2018), and no group of more than 50 (Zagorodniuk 2018) has been recorded. The larger groups (more than 50 individuals) of P. k. lepidus reported in this paper (Fig.…”
Section: Structure and Sex Ratiomentioning
confidence: 99%